EVALUATION OF REPLADING NIGELLA SATIVA SEEDS IN THE RATION OF GROWING RABBITS AND ITS EFFECT ON PRODUCTIVE PERORMANCE AND DIGESTION COEFFICIENT OF RATION NUTRIENTS - N. M. Abdullah (Mesopotamia Journal of Agriculture)
Fifteen local breed male rabbits 8 weeks aged were allocated into three groups. In order to study the effect of using Nigella Sativa seeds in their rations on productive performance, carcass traits and digestibility. The first group was fed standard ration according to (NRC, 1994), containing 15.6% crude protein 2243 kcal/kg. ME, and 10% soybean meal (SBM), while the second and third groups were fed the same ration with exception of partial replacement of (SBM) in a ratio of 2 and 4% by Nigella Sativa L. seeds (NSS), respectively. The feeding trial lasted for eight weeks, the amounts of ratio consumed and weight gained were determined weekly. At the last week of feeding period all feces produced from each group were collected, then all rabbits were slaughtered and carcass measurements were taken. There were no statistical differences among the groups in the average of final wt. and total wt. gain, the feeding conversion ratio was improved at 22% for the groups which were fed rations with NSS when compared with the group fed standard ration. However there were no statistical differences amongst all groups concerning carcass measurements. The results indicated an improvement in the dry matter and the other nutrients digestibility for rabbits consuming ration containing NSS. In conclusion the addition of NSS at 4% in the ration of local rabbits improve the values of productive parameters, carcass traits and nutrients digestibility.